2016
DOI: 10.1111/soc4.12358
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Violence against Rural Women: The Current and Future State of Feminist Empirical and Theoretical Contributions

Abstract: Rural crime in general ranks among the least studied social problems in the social sciences; however, a growing body of research shows that rural woman abuse is a major problem. The current state of progressive critical feminist social scientific knowledge enhances an empirical and theoretical understanding of intimate violence against rural women. Revealing the complexities of rural women's experiences and struggles with violent relationships reconstitutes violence against women as a public crisis that requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 45 publications
(66 reference statements)
0
9
0
Order By: Relevance
“…Though the back-talk interview schedule did not include specific questions about pornography, most of the participants reported experiences with various types of it, mirroring several themes uncovered in the ROSA study. The back-talk approach is a recent development in qualitative social sciences (Hall-Sanchez, 2013). Yet, “back-talk” as a display of resistance or form of opposition in narrative has deep roots in African American history (Collins, 2000).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Though the back-talk interview schedule did not include specific questions about pornography, most of the participants reported experiences with various types of it, mirroring several themes uncovered in the ROSA study. The back-talk approach is a recent development in qualitative social sciences (Hall-Sanchez, 2013). Yet, “back-talk” as a display of resistance or form of opposition in narrative has deep roots in African American history (Collins, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…Back-talk interviews empower participants, providing opportunities to exercise a greater role in the research processes. Scholars can also responsibly disseminate sensitive issues to potentially diverse and highly politicized audiences, contributing to a more reflexive and socially responsible research culture (Frisina, 2006; Hall-Sanchez, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…Rural violence has emerged as an important field of inquiry over the last few decades (for overviews, see Edwards, 2015;Hall-Sanchez, 2016;. This research has shown that physical and sexual violence is just as commonif not more commonin rural areas as it is in urban areas (Edwards, 2015), and that such violence has specific rurality-based characteristics.…”
Section: Sexual Violence and Ruralitymentioning
confidence: 99%
“…Whilst the lives of people with disability residing in rural areas are also subject to perceptions about loneliness and as outcast from the community, such perceptions are not always accurate, however the identities "marked by disability [are nonetheless] complex and multilayered" (Soldatic & Johnson, 2017, p. 245). In researching gendered crimes in rural settings, scholars have highlighted the significance of rurality and place in understanding the prevalence, severity, reporting of family violence, and the justice and service system response to women who experience family violence (George & Harris, 2014;Pruitt, 2008) and intimate partner violence (DeKeseredy, 2019;Hall-Sanchez, 2016;Rennison, DeKeseredy & Dragiewicz, 2013). While the crime perpetrated against Noah was not gendered in nature, it is argued that the dimensions of disability and how his disability was understood and responded to within a rural context had repercussions that affected the outcome of his case.…”
Section: Intersectionality Of Victimisation Disability and Ruralitymentioning
confidence: 99%